Do Probiotics Have a Part in Dentistry and Dental Care? (International Journal of Food and Nutritional Sciences, 2022)
This review discusses the most recent research on probiotic bacteriotherapy from the standpoint of dental health. Recent experimental research and the outcomes of randomised controlled trials have demonstrated that some species of gut bacteria, particularly Lactobacillus and Bifidobacterium, may have positive effects on the oral cavity by suppressing cariogenic streptococci and Candida sp. gastrointestinal illnesses have been successfully managed using probiotics. Additionally, they seem to reduce allergies and disorders with immunological pathology symptoms. The mechanisms of probiotic effect seem to be related to immune regulation and colonisation resistance. Different antimicrobial compounds, including organic acids, hydrogen peroxide, carbon peroxide, diacetyl, low molecular weight antimicrobial chemicals, bacteriocins, and adhesion inhibitors, which can have an impact on oral microbiota, can be produced by lactic acid bacteria. On the probiotic effect in the oral cavity, there is still a lack of information. It is necessary to learn more about how probiotics colonise in the mouth and any potential effects they may have on and within oral biofilms. There is every reason to think that the hypothesised probiotic mechanisms of action in the mouth and other gastrointestinal tract regions are same.Probiotic therapy is an intriguing and topical idea that deserves additional investigation in the realms of oral medicine and dentistry given the growing global problem of antimicrobial antibiotic resistance.